Phyllanthus fluitans (Phyllanthaceae): a new record of an aquatic plant for the flora of Panama - Ibáñez García, Alicia; Flores, Rodolfo (Instituto de Ecología, A.C., 2020)
Background and Aims: Phyllanthus fluitans is the only aquatic free-floating species in the family Phyllanthaceae. It occurs in South American wetlands and has also been reported in Mexico, where it is considered non-native. It is used as an aquarium plant and has escaped cultivation in Florida (USA). The objective of this study is to report the presence of this species in Panama, collected in the Matusagaratí complex of wetlands, in the Darién Province.Methods: This work is based on floristic field surveys in Matusagaratí, during both the dry and wet seasons, study of specimens and consultation of relevant literature. A general distribution map of the species is drawn based on GBIF data and its conservation status in Panama is assessed according to IUCN criteria.Key results: This is the first record of the aquatic plant Phyllanthus fluitans in Panama. The distribution of the species is discussed in the light of this new finding. Data on the ecology of the species in Panama are presented.Conclusions: The presence of Phyllanthus fluitans is confirmed in Panama, representing an extension of the natural range of the species. Only one population has been found in an herbaceous seasonally flooded habitat that is periodically burned. In our national conservation analysis, we recommend the species to be considered as Endangered (EN), and this population to become a conservation target. This study reaffirms the importance of carrying out explorations in botanically poorly known regions, such as the Darién.